2015
DOI: 10.1099/jmm.0.000108
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and bacteriological characterization of neonatal porcine diarrhoea of uncertain aetiology

Abstract: Neonatal porcine diarrhoea of uncertain aetiology has been reported from a number of countries. This study investigated 50 diarrhoeic and 19 healthy piglets from 10 affected Swedish herds. The piglets were blood-sampled for analysis of serum c-globulin and necropsied, and the intestines were sampled for histopathology and cultured for Escherichia coli, Clostridium perfringens and Clostridium difficile. Escherichia coli isolates (n5276) were examined by PCR for virulence genes encoding LT, STa, STb, EAST1, VT2e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 36 publications
9
25
0
1
Order By: Relevance
“…It has been established that C. difficile can cause enteritis in neonatal piglets [2729], but epidemiologic studies do not support the idea of C. difficile being a primary diarrhoeic pathogen in pigs [4, 13, 3032]. In accordance with this, the detection of C. difficile was not associated with being a case in this study.…”
Section: Discussionsupporting
confidence: 61%
“…It has been established that C. difficile can cause enteritis in neonatal piglets [2729], but epidemiologic studies do not support the idea of C. difficile being a primary diarrhoeic pathogen in pigs [4, 13, 3032]. In accordance with this, the detection of C. difficile was not associated with being a case in this study.…”
Section: Discussionsupporting
confidence: 61%
“…The concentrations of porcine IgG in the piglets serum are shown in table 2. Discussion Diarrhea in newborn piglets is an old but still relevant problem in pig production (Larsson, 2016). In this study, diarrhea was the visible symptom in agreement with results obtained later by Agbokounou et al (2017a) who showed that diarrhea is the visible symptom observed with local piglets fed for the first 48 h of life with either heated bovine colostrum, or thawed bovine colostrum and thereafter kept under the sow piglets, or colostrum from the mother.…”
Section: Immune Transfer To Pigletssupporting
confidence: 81%
“…According to these observations, diarrhea observed between 7 and 14 d in the piglets of SCB group could not be attributed to low colostrum intake. The composition of the intestinal microflora has been reported to show a large inter-individual variability during the first 1-2 weeks of the piglet's life, followed by a cohabitation effect around 3-4 weeks when the microflora among piglets become alike (Larsson, 2016). These findings could explain the only prevalence of diarrhea in the piglets of SCB group.…”
Section: Immune Transfer To Pigletssupporting
confidence: 54%
See 2 more Smart Citations